Healthy Eating: The Importance of Eating - Emily Minton (EDIS)
Eating healthy is one of the key ingredients to staying healthy. Complete the fill-in-the-blank activity and reveal the hidden message! This 2-page handout was written by Emily Minton and published by the UF Department of Family, Youth and Community Sciences, March 2012.